Boundary talk in Life (dis)Orientation: Collaborative conversations across Higher Education Institutions - Janet Jarvis; Sarina de Jager (The Journal for Transdisciplinary Research in Southern Africa, 2021)
Life Orientation (LO) as a compulsory subject in the South African school curriculum (Grades 7–12) aims to develop the learner’s self-in-society. This implies a holistic approach that includes the personal, social and physical development of the learner. In most Higher Education Institutions (HEIs), LO is not offered as a specialisation that includes these three broad aspects of development. In many cases, the emphasis rests with personal development, focusing, in particular, on modules taken in Psychology. Physical Education, if it is included in any LO programme, usually falls within the ambit of Sports/Human Movement Science programmes. The social development aspect is, by and large, omitted and Human Rights Education, including Religion Education and Citizenship Education, is neglected. Alternatively, pre-service teachers are required to select from a smorgasbord of modules and they often graduate without having included all three broad aspects of this specialisation. This article speaks to the importance of collaborative relationships across HEIs with a view to meaningful boundary talk that can be transformative in nature and provide the platform for research ventures. This collaboration that commenced as a community of two in conversation, led to a community of many in conversation, in the form of a national colloquium in 2020 that focused on LO in the HEI space. This article presents the themes emerging from this colloquium and recommends that transdisciplinary knowledge can lead to transdisciplinary education that serves the mandate of the LO specialisation in HEIs, namely, to prepare pre-service LO teachers.